2022
DOI: 10.5194/egusphere-2022-998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signatures of the Madden-Julian Oscillation in Middle Atmosphere zonal mean Temperature: Triggering the Interhemispheric Coupling pattern

Abstract: Abstract. The Madden–Julian oscillation (MJO) is the dominant mode of intraseasonal variability in the troposphere. The influence of the MJO on the middle atmosphere (MA) and particularly on its temperature is of interest for both the understanding of MJO-induced teleconnections and research on the variability of the middle atmosphere. However, only few studies dealing with the influence of the MJO on MA temperature are available. We analyze statistically the connection of the MJO and the MA zonal mean tempera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Garfinkel et al, 2012;Yang et al, 2019). As noted previously, the recent study by Hoffmann et al (2022) suggests that the MLT region is also affected by the MJO via the interhemispheric coupling mechanism.…”
Section: Qbo and Mjo Signaturessupporting
confidence: 52%
See 1 more Smart Citation
“…Garfinkel et al, 2012;Yang et al, 2019). As noted previously, the recent study by Hoffmann et al (2022) suggests that the MLT region is also affected by the MJO via the interhemispheric coupling mechanism.…”
Section: Qbo and Mjo Signaturessupporting
confidence: 52%
“…The interhemispheric coupling phenomenon is particularly relevant for the variability in the NLCs or PMCs in the polar summer mesopause, and this has been used in several pioneering studies (Gumbel and Karlsson, 2011;Karlsson et al, 2007). The typical interhemispheric coupling pattern in the middle-atmospheric temperature field may be triggered by altered planetary wave activity and/or stratospheric warmings and has also recently been proposed to be present in observational data in the context of a possible Madden-Julian oscillation (MJO) signature in the middle atmosphere (Hoffmann et al, 2022). In addition, it has been suggested that the thermodynamical effects of volcanic eruptions may affect the interhemispheric coupling pattern (Wallis et al, 2023).…”
Section: Inter-and Intrahemispheric Couplingmentioning
confidence: 99%
“…Garfinkel et al (2012); Yang et al (2019)). The recent study by Hoffmann et al (2022) suggests that the MLT region is also affected by the MJO via the interhemispheric coupling mechanism.…”
Section: Qbo and Mjo Signaturesmentioning
confidence: 98%
“…The interhemispheric coupling phenomenon is particularly relevant for the variability of NLC/PMCs in the polar summer mesopause and this has been used in several pioneering studies (Gumbel and Karlsson, 2011;Karlsson et al, 2007). The typical interhemispheric coupling pattern in the middle atmospheric temperature field may be triggered by altered planetary wave activity and/or stratospheric warmings, and has also recently been identified in experimental data in the context of a possible Madden-Julian-Oscillation (MJO) signature in the middle atmosphere (Hoffmann et al, 2022). In addition, the dynamical/thermal effects of volcanic eruptions may impact on the interhemispheric coupling pattern (Wallis et al, 2023).…”
Section: Inter-and Intra-hemispheric Couplingmentioning
confidence: 99%